Electrochemical Analysis of Antichemotherapeutic Drug Zanosar in Pharmaceutical and Biological Samples by Differential Pulse Polarography - Chennupalle Nageswara Reddy; Puthalapattu ReddyPrasad; NeelamYughandhar Sreedhar (Journal of Analytical Methods in Chemistry)
The electrochemical reduction of zanosar was investigated systematically by direct current polarography, cyclic voltammetry, and differential pulse polarography (DPP). A simple DPP technique was proposed for the direct quantitative determination of anticancer drug zanosar in pharmaceutical formulation and spiked human urine samples for the first time. The reduction potential was −0.28 V versus Ag/AgCl with a hanging mercury drop electrode in Britton-Robinson buffer as supporting electrolyte. The dependence of the intensities of currents and potentials on pH, concentration, scan rate, deposition time, and nature of the supporting electrolyte was investigated. The calibration curve was found to be linear with the following equation: y=0.4041x+0.012, with a correlation coefficient of 0.992 (R2) over a concentration range from 1.0×10-7 M to 1.0×10-3 M. In the present investigation, the achieved limit of detection (LOD) and limit of quantization (LQD) were 7.42×10-8 M and 2.47×10-8 M; respectively. Excipients did not interfere with the determination of zanosar in pharmaceutical formulation and spiked urine samples. Precision and accuracy of the developed method were checked by recovery studies in pharmaceutical formulation and spiked human urine samples.